Mental health care provided to patients admitted to Brazilian psychiatric institutes: a scoping review - Lannuzya Veríssimo e Oliveira; Pétala Tuani Cândido de Oliveira Salvador; Claúdia Helena Soares de Morais Freitas
ABSTRACT Objective: to identify and map the mental health care offered to patients admitted to forensic psychiatry institutes in Brazil. Method: a scoping review was guided by the JBI Institute Reviewer's Manual. Searches took place in February 2019, in six databases, using descriptors and synonyms. Analysis was performed using simple descriptive statistics. Results: twelve studies were included, which were predominantly dissertations, published in 2014, carried out in the southeastern region of Brazil. Qualitative researches in the field of psychology and law stood out, with emphasis on the speeches of health professionals, and which did not specify the methodology of data analysis. Final considerations: the care provided to interns of the institutions has a punitive character, is based on excessive medicalization and diverges from the current legislation, which makes social reintegration difficult.